Analysis of Factors Affecting Student Tax Compliance in Batam City - Angel Claudia Tissany Wijaya; Ria Karina; Sumantri Sumantri (Universitas Internasional Batam, 2022)
This study aims to understand the influence of the independent variables of tax morale, tax justice, trust in the government, power of authority, tax complexity, tax information, and tax awareness on tax compliance. In Indonesia, the level of tax compliance is very low. This is evidenced by looking at the level of Indonesia's tax ratio. As a taxpayer, of course, you must comply with every tax payment process and tax reporting. By understanding the factors of tax compliance, it is expected to be able to overcome what is lacking in each taxation scope so as to increase the level of tax compliance and build the country's economy. This study uses a questionnaire method in the form of distributing questionnaires or a collection of questions to 100 respondents as representatives. The respondents came from students who are still active in lectures and already have a TIN. The results of the questionnaire will be tested using the SPSS program to determine whether or not the independent variable has a significant effect on tax compliance as the dependent variable. The results of this study indicate that 4 of the 7 independent variables studied have a significant positive effect on tax compliance. 2 variables have a significant negative effect on tax compliance. 1 other variable does not have a significant effect on tax compliance.